2017
DOI: 10.1002/jocb.201
|View full text |Cite
|
Sign up to set email alerts
|

Creativity and the Genome: The State of Affairs

Abstract: This essay is focused on the research into the genetic etiology of creativity and related processes. In an attempt to identify the most salient points of this research, the article provides a brief overview of quantitative‐genetic (family and twin) and molecular‐genetic (candidate‐gene and whole‐genome) studies of creativity. To conclude, the essay formulates a future agenda for this subfield of scientific inquiry into creativity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…One critical step towards a better understanding of creativity is to unveil its underlying genetic architectures. Many studies reported the first candidate genes for creativity (Reuter et al, 2006; Runco et al, 2011; Zhang et al, 2014a, b; Zabelina et al, 2016; Grigorenko, 2017; see Table 1).…”
Section: Genetic Research Reveals a Strong Association Between Da Actmentioning
confidence: 99%
“…One critical step towards a better understanding of creativity is to unveil its underlying genetic architectures. Many studies reported the first candidate genes for creativity (Reuter et al, 2006; Runco et al, 2011; Zhang et al, 2014a, b; Zabelina et al, 2016; Grigorenko, 2017; see Table 1).…”
Section: Genetic Research Reveals a Strong Association Between Da Actmentioning
confidence: 99%